A STRATEGIC PERSPECTIVE ON FOOD INDUSTRY CHALLENGES - Suganthi S; Santhanakrishnan K; Vijaya Krishanan; Pradeepa A K; Paranthaman (The Bioscan, 2025)
The global food industry faces an evolving landscape of challenges driven by shifting consumer demands, regulatory pressures, supply chain disruptions, climate change, and emerging technologies. This paper provides a strategic perspective on these critical issues, examining their implications for food safety, sustainability, economic resilience, and technological adoption. It highlights key stressors such as labor shortages, traceability requirements, antimicrobial resistance, and the growing need for digital transformation across the food supply chain. By exploring both risks and opportunities, the analysis offers insights into how stakeholders—producers, processors, policymakers, and consumers— can collaboratively address these challenges through innovation, regulatory alignment, and sustainable practices. Strategic foresight and cross-sector collaboration are essential to ensure the industry's adaptability and long-term viability in a rapidly changing global context.